2017
DOI: 10.1590/1516-4446-2015-1894
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine-type stimulant use and conditional paths of consumption: data from the Second Brazilian National Alcohol and Drugs Survey

Abstract: Brazil presents high rates of ATS use. Prevention and treatment strategies should focus on the protective effect of higher education levels and should target polydrug use. Knowledge of ATS-associated factors and user profiles is the starting point for developing effective treatments and tailored prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Polydrug use involving psychostimulants poses significant public health risks. For example, one study showed that amphetamine users were 21 times more likely to have a concurrent cannabis use disorder and 7 times more likely to have past-year concurrent cocaine use, compared to those with no prior history of amphetamine use (Massaro et al, 2017). In addition, nearly one-third of overdose deaths involved both psychostimulants and opioids, such as heroin and fentanyl (Kariisa et al, 2019).…”
Section: Psychostimulantsmentioning
confidence: 99%
“…Polydrug use involving psychostimulants poses significant public health risks. For example, one study showed that amphetamine users were 21 times more likely to have a concurrent cannabis use disorder and 7 times more likely to have past-year concurrent cocaine use, compared to those with no prior history of amphetamine use (Massaro et al, 2017). In addition, nearly one-third of overdose deaths involved both psychostimulants and opioids, such as heroin and fentanyl (Kariisa et al, 2019).…”
Section: Psychostimulantsmentioning
confidence: 99%
“…There has been an increasing trend of amphetamine use in many parts of the world in recent years (1,2). Amphetamines negatively affect the productivity, health and social wellbeing, and criminal status of their users (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The main contributing factors of MDD are the use of ATS for the past three months, the low and moderate social support from family and significant others as well as a CD4 count less than 350 cells/ul. ATS drugs include amphetamine, methamphetamine and ecstasy or 3,4methylenedioxyethylamphetamine (MDMA) (Massaro et al, 2017). The ATS recent use increases about 40-fold of chances for RVD patients to get MDD.…”
Section: Discussionmentioning
confidence: 99%